An Analysis of the Determinant Factors of Poverty and Inequality in Indonesia and Their Implications for Village Development Planning - Wedi, Agus; Fathurrahman, Reza (Borong Newinera Publisher, 2025)
This study aims to analyze the key determinant factors influencing poverty and inequality, as well as to examine their implications for village development planning. The research adopts a mixed-method approach by integrating robust regression-based quantitative analysis with qualitative literature studies derived from secondary sources. The findings identify five factors that significantly affect inequality: economic growth, the open unemployment rate, the human development index (HDI), the proportion of informal agricultural workers, and fiscal transfers from the central government to regional administrations. Furthermore, six determinant factors are found to influence poverty: economic growth, inequality, the open unemployment rate, the human development index, the proportion of informal agricultural workers, and fiscal transfers from the central government to local governments. As a key implication, the study emphasizes the need to prioritize the allocation of village funds toward programs that directly address the root causes of poverty and inequality. This strategic focus is essential to ensure that rural development planning contributes effectively to social equity and sustainable economic growth at the village level.